2002
DOI: 10.1002/pi.895
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high electrical fields on ageing and polarization properties of polyethylene

Abstract: The influence of high electrical fields (above 20  kV mm−1) on ageing, polarization and morphology of polyethylene (PE) is discussed. Infrared and positron annihilation spectroscopy measurements together with capacitance measurements tend to indicate that polymer morphology is modified by high fields. We show that accelerated electrical ageing characteristics of PE are directly linked to morphology changes induced by the field. Below a so‐called critical field, the activation volume of the ageing process is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…While macroscopic electrical degradation features, such as electrical trees, are reasonably wellunderstood, this is not the case for precursor phenomena, where a number of different processes have been suggested to lead to the modification of the material at the nanoscopic level. These include: chain scission at electric fields >20 kV/mm and consequent formation of sub-microcavities causing local accumulation of space charge [10]; charge recombination and consequent electroluminescence leading to local degradation through photo-oxidation [11]; field-induced mechanical stress and consequent propagating cracking associated with breaking of inter-lamellar tie chains [12].…”
Section: Introductionmentioning
confidence: 99%
“…While macroscopic electrical degradation features, such as electrical trees, are reasonably wellunderstood, this is not the case for precursor phenomena, where a number of different processes have been suggested to lead to the modification of the material at the nanoscopic level. These include: chain scission at electric fields >20 kV/mm and consequent formation of sub-microcavities causing local accumulation of space charge [10]; charge recombination and consequent electroluminescence leading to local degradation through photo-oxidation [11]; field-induced mechanical stress and consequent propagating cracking associated with breaking of inter-lamellar tie chains [12].…”
Section: Introductionmentioning
confidence: 99%
“…In general, initiation is believed to involve the chemical and physical modification of the pristine polymer through the formation of defective regions at the nano-and micro-scales [17]. Crine [18] suggested that the initial stage of degradation under a high electric field (>20 kV mm −1 ) involves chain scission, the formation of free radicals and the generation of submicrocavities. Local accumulation of space charge (SC) then occurs, which increases the local electric field such that ageing is accelerated to failure.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of polymer ageing and its effect on the electrical behaviour of polymers have been reported. For example, it has been suggested that ageing is initiated at applied electric fields in excess of ∼20 kV/mm through chain scission processes, free radical generation, the formation of submicro‐cavities and the consequent accumulation of space charge [10]. This association of free volume and charge trapping is supported by a complementary theoretical study [11, 12].…”
Section: Introductionmentioning
confidence: 98%